2011
DOI: 10.1002/star.201100073
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous synthesis and characterization of starch acetates in ionic liquid without catalysts

Abstract: Homogeneous modification of corn starch with acetic anhydride was performed in ionic liquids 1-butyl-3-methylimidazolium chloride (BMIMCl) without catalysts. The results indicated that the pretreatment of starch, which starch was dissolved in BMIMCl at 1058C for 2 h before reaction, provided feasible reaction environment for starch functionalization. Optimum modification conditions for maximum degree of substitute (DS 2.11) were shown as following: acetic anhydride/anhydroglucose units (AGU) molar ratio 5:1, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…The entire loss of granular nature of the starch confirms relatively high degree of substitution [35]. According to the SEM profiles, the starch granules were mostly converted from their crystalline structure into amorphous state during the dissolution processes, which led to the uniform esterification reaction conducted under conditions involved [37,49]. The solvent DMSO used as reaction medium during the modification reaction was responsible for disruption the hydrogen bond of starch, sequentially led to the destruction of the crystalline structure of starch granules.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 84%
“…The entire loss of granular nature of the starch confirms relatively high degree of substitution [35]. According to the SEM profiles, the starch granules were mostly converted from their crystalline structure into amorphous state during the dissolution processes, which led to the uniform esterification reaction conducted under conditions involved [37,49]. The solvent DMSO used as reaction medium during the modification reaction was responsible for disruption the hydrogen bond of starch, sequentially led to the destruction of the crystalline structure of starch granules.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 84%
“…Acetylation percentage denoted the same trending with. It could be expected for increasing pH releasing hydrolysis reaction regard with decreasing acetyl group and increasing residual acetic acid in the bulk liquid [27][28]. Increasing pH may affect starch to undergo partial gelatinization under alkaline resulting high solubility.…”
Section: Degree Of Substitutionmentioning
confidence: 99%
“…The desired starch acetylation reaction is accompanied by hydrolysis reaction of the acetylated starch after 40-50 minutes acetylation, which is indicated by the decreasing value of degree of substitution and the increasing concentration of residual acetic acid in the bulk liquid. Luo and Zhou [15] reported that the lower the concentration of acetyl groups in the starch acetate with increasing reaction time is caused by hydrolysis of the ester starch (starch acetate) produced or elimination reactions as a result of excess water (from starch and byproducts esterification) are not discharged from the reactor during the reaction. Table 1 shows that the value of mass transfer rate constant (Kcs) is smaller than chemical reaction constant (k).…”
Section: Effect Of the Glacial Acetic Acid/ Gadung Flourmentioning
confidence: 99%
“…Song et al [19] reported that at pH 9.5, side reaction (acetate starch hydrolysis) will be the dominant reaction. Luo and Zhou [15] reported that the lower value of acetyl groups concentration in the starch acetate with increasing reaction time is mainly caused by hydrolysis of the starch ester (starch acetate). This hydrolysis reaction is likely to happen due to excess water in the system, which comes from moisture of the starch and byproducts esterification.…”
Section: Effect Of Phmentioning
confidence: 99%